Pregnancy Exercise and Old Labour Stage II in RSU PKU Muhammadiyah Bantul in Year 2009 - Estin Nugrahani; Asmar Yetty Zein; Nining Wiyati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
One of causes of high maternal mortality in Indonesia and the developing world is long deliveries. Pregnancy exercise can reduce the risk of long deliveries. Based on preliminary studies in PKU Muhammadiyah Hospital in Bantul, there were 139 mothers who gave birth in January to March 2009, by cesarean section as many as 47 people, 54 normal deliveries, and vacuum extraction of 38 people. There are 28 mothers maternity pregnancy exercise in which 21 (75%) normal childbirth with a long second stage of labor on average 2 hours in primigravida and 1 hour on multigravida, while 7 people (25%) with delivery action of Vacum Extraction and cesarean section. To determine the frequency relationship with old pregnant gymnastic second stage of labor. Analytical observational. The design of this study using cross-sectional. All mothers who do gymnastics normal pregnancy and childbirth in RSU PKU Muhammadiyah Bantul. Samples were taken in total sampling. Data were analyzed using Pearson Product Moment. The majority of respondents did pregnancy exercise 14-27 times and the second stage of labor was not a majority t.for long. Based on this study there is a relationship means that the more often the frequency of pregnancy exercise more and no longer second stage labor. Conclusion: There is a relationship between the frequency of pregnancy exercise with a long second stage of labor